2015
DOI: 10.1371/journal.pone.0142829
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell Porosity Provides Insight on Evolution of Nesting in Dinosaurs

Abstract: Knowledge about the types of nests built by dinosaurs can provide insight into the evolution of nesting and reproductive behaviors among archosaurs. However, the low preservation potential of their nesting materials and nesting structures means that most information can only be gleaned indirectly through comparison with extant archosaurs. Two general nest types are recognized among living archosaurs: 1) covered nests, in which eggs are incubated while fully covered by nesting material (as in crocodylians and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
74
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 88 publications
1
74
0
1
Order By: Relevance
“…Speculation that neonates of large ornithischian dinosaurs (e.g., ceratopsians and hadrosaurids) made 2,600-to 3,200-km migrations from lower latitude nesting grounds to rich summer feeding grounds in the Arctic may have been infeasible because of unexpectedly short posthatching windows for seasonal travel (75)(76)(77). Finally, hypotheses regarding nest microenvironment (43, 61), eggshell gas conductance (61,78,79), embryonic physiology (45), reproductive effort, annual numbers of clutches and taxon generation times (21,80,81), and developmental mode (43) can be strengthened or formally tested in light of slower in ovo dinosaur development. These results may have implications for nonavian dinosaur extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Speculation that neonates of large ornithischian dinosaurs (e.g., ceratopsians and hadrosaurids) made 2,600-to 3,200-km migrations from lower latitude nesting grounds to rich summer feeding grounds in the Arctic may have been infeasible because of unexpectedly short posthatching windows for seasonal travel (75)(76)(77). Finally, hypotheses regarding nest microenvironment (43, 61), eggshell gas conductance (61,78,79), embryonic physiology (45), reproductive effort, annual numbers of clutches and taxon generation times (21,80,81), and developmental mode (43) can be strengthened or formally tested in light of slower in ovo dinosaur development. These results may have implications for nonavian dinosaur extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Although calculation of gas and water conductance is not possible due to the fragmentary nature of all eggshells, the thinness of MT I combined with a moderate to high density of pores and blindly ending pneumatic cavities (Table 2), and the wide pores relative to overall shell thickness suggest that the eggs were deposited in a buried nest, as reconstructed for most dinosaurs (Williams et al 1984;Horner 2000;Deeming 2006), and probably representing the ancestral mode of egg-laying (Tanaka et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, carnivorous dinosaurs could have dispersed seeds, either by accidental consumption of seeds or via their consumption of herbivorous animals; this has been confirmed in some extant vertebrates (Nogales et al , van Leeuwen et al ). Theropod dinosaurs are direct ancestors of extant birds, and therefore, extrapolations based on trait allometry for extant birds is a commonly used and effective approach for estimating these dinosaurs’ traits (Sato et al , Tanaka et al ). Although extant crocodiles, which are descendants of archosaurs, are occasionally used to infer the ecology of extinct dinosaurs (Seebacher et al ), recent advances in dinosaur ecology have demonstrated that extant birds are closer to theropod dinosaurs in their physiology, such as homeothermy, their behaviour (Gillooly et al ), diversified diets (Zanno and Makovicky ) and bipedal locomotion (Farlow et al ).…”
Section: Methodsmentioning
confidence: 99%